Diversity of the fungal community on mango associated with stem end rot and anthracnose diseases based on amplicon targeted metagenomics - Ani Widiastuti; Suryanti; Alvina Clara Giovanni; Niken Rasmi Paramita (Journal of Plant Protection Research, 2024)
This study aimed to comprehend the diversity of the fungal community on Chokanan mango, a premium mango variety from Thailand which is widely cultivated in Indonesia, associated with stem end rot and anthracnose disease using high-throughput amplicon targeted metagenomics analysis by next-generation sequencing (NGS). Samples used in this study were freshly harvested healthy fruits at the age of 15-weeks (H15.ITS), healthy fruits after 2 weeks incubation (H17.ITS), 17-week old fruits (S17.ITS) with stem end rot symptoms, and 17-week old fruits (A17.ITS) with anthracnose symptoms. Results showed that the Basidiomycota phylum was dominant in the healthy fruits, while the Ascomycota phylum was found dominantly in sick fruits. Based on OTUs alignment of sequenced data, some species found to be dominantly associated with stem end rot disease in this study were Lasiodiplodia theobromae, Neofusicoccum cordaticola and N. mangiferae. Dominant species which were associated with mango anthracnose disease were Colletotrichum gloeosporioides, Botryosphaeria corticis, Volutella sp., and Pseudofusicoccum violacearum. These fungal genera were not found to be dominant in healthy fruits at the same age indicating that specific genera contributed to developing postharvest diseases on mango differently. The findings confirmed that the fungal community associated with stem end rot and anthracnose disease on mango was unique, and specific species contributed in particular disease development. Since mango is an important global commodity, these research findings will contribute significantly to global biosecurity.